Penentuan Prioritas Perbaikan Kualitas Layanan TransJakarta dengan Menggunakan Metode IPA-PGCV - Sukwadi, Ronald; Jufina, (Universitas Katolik Parahyangan, 2015)
TransJakarta was a Bus Rapid Transit (BRT) system in Jakarta. It was designed to provide Jakartacitizens with a fast public transportation system to help reduce rush hour traffic. After operating more thanone decade, many suggestions and critics were given related to service quality. IPA and PGCV methods wereapplied to determine which service attributes should be improved and their priorities. In this research, eightservice attributes were identified as critical attributes (on first quadrant of IPA diagram). The higher value ofPGCV index indicated the priority level of attributes. Based on its priority level, the order were 1) easinessof giving suggestions, 2) ticket queue, 3) easiness of complaints, 4) the facilities for passengers with specialneeds, 5) employees appearance, 6) transportation cost, 7) accessibility, and 8) the number of bus.